The Brassica napus wall‐associated kinase‐like (WAKL) gene Rlm9 provides race‐specific blackleg resistance. (7th October 2020) - Larkan, Nicholas J.; Ma, Lisong; Haddadi, Parham; Buchwaldt, Miles; Parkin, Isobel A.P.; Djavaheri, Mohammad; Borhan, M. Hossein
SUMMARY: In plants, race‐specific defence against microbial pathogens is facilitated by resistance ( R ) genes which correspond to specific pathogen avirulence genes. This study reports the cloning of a blackleg R gene from Brassica napus (canola), Rlm9, which encodes a wall‐associated kinase‐like (WAKL) protein, a newly discovered class of race‐specific plant RLK resistance genes. Rlm9 provides race‐specific resistance against isolates of Leptosphaeria maculans carrying the corresponding avirulence gene AvrLm5‐9, representing only the second WAKL‐type R gene described to date. The Rlm9 protein is predicted to be cell membrane‐bound and while not conclusive, our work did not indicate direct interaction with AvrLm5‐9. Rlm9 forms part of a distinct evolutionary family of RLK proteins in B. napus, and while little is yet known about WAKL function, the Brassica – Leptosphaeria pathosystem may prove to be a model system by which the mechanism of fungal avirulence protein recognition by WAKL‐type R genes can be determined. Significance Statement: Rlm9 encodes a wall‐associated kinase‐like (WAKL) race‐specific resistance protein, is a member of an emerging class of race‐specific plant receptor‐like kinase resistance genes and is the first of its kind to be cloned from a dicot species.